Naskah Mawahib Rabb al-Falaq: Melacak Titik Temu Ajaran Dua Tarekat (Syaziliyah dan Naqsyabandiyah) di Minangkabau - Syofyan Hadi (Jurnal Lektur Keagamaan, 2013)
Mawahib rabb al-falaq bi-syarh qasidah binti al-milaq is the book of Sufism and the teaching of Naqsyabandiyah school of thought. This book showed us there was any dialogical process of the Sufism development in Indonesia. On this scripts, it was found the turning point of the teachings of both Naqsyabandiyah developed by Syekh Isma’il al-Khalidi al-Minangkabawi and the teaching of Syaziliyah order. That turning point occurs in some aspects of teachings, such as the rabitah concept, mursyid of kamil mukammil, the concept of ma’rifah, the firmness in holding Shari’a, views on Wali Allah. The author, Syekh Isma’il was the follower of the teaching of the Syaziliyah order, besides he was also recognized as he central figure of Naqsyabandiyah order in Archipelago. Keywords: mawahib, turning point of the teaching, Naqsyabandiyah, Syaziliyah